2001
DOI: 10.1046/j.1365-2540.2001.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

P elements and P-M characteristics in natural populations of Drosophila melanogaster in the southernmost islands of Japan and in Taiwan

Abstract: In order to study P element dynamics in natural populations of Drosophila melanogaster, 126 isofemale lines were examined from seven of the southernmost islands of Japan (the Sakishima Islands) and from Taiwan. Gonadal dysgenesis (GD) tests showed large divergences in the P-M phenotypes (P inducing and P repressing abilities) between the island populations. The P-M characteristics of each population, however, had not greatly changed in the past 15 years. Their genomic P element pro®les are highly similar, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…The P activity was negatively correlated with the number of KP elements. However, such correlation was not observed in D. melanogaster samples from Japan and Tawain (Itoh et al, 2001). This absence of a clear relationship between the P-M phenotypes and the genomic P element composition seems to be common.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The P activity was negatively correlated with the number of KP elements. However, such correlation was not observed in D. melanogaster samples from Japan and Tawain (Itoh et al, 2001). This absence of a clear relationship between the P-M phenotypes and the genomic P element composition seems to be common.…”
Section: Discussionmentioning
confidence: 79%
“…Other internally deleted elements also occur, but in lower numbers, as deduced from the signal intensity of the bands between those of 2.2 and 0.42 kb. The predominance of full-sized P plus KP elements in the genomes of most populations around the world has been pointed out by Itoh and collaborators (Itoh and Boussy, 2002;Itoh et al, 2001), based on their own surveys or on other authors (Boussy et al, 1988;Nitasaka and Yamazaki, 1994;Bonnivard and Higuet, 1999;French et al, 1999;Itoh et al, 2001;Itoh and Boussy, 2002). Itoh and Boussy (2002) wondered whether this could be the final equilibrium state of the D. melanogaster genomes in nature, and suggested that further surveys of wild populations are required.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, four HT isofemale lines demonstrate a novel phenotype, which is designated as H 0 (Figure 1a). H 0 strains have high hoboactivity potential and low hobo-repression potential, like the P 0 strains hypothesized in the P-M system (Quesneville and Anxolabehere, 1998) and found in a natural population by Itoh et al (2001).…”
Section: Resultsmentioning
confidence: 73%
“…We have examined the dynamics of hobo elements in Japanese natural populations of laboratory-maintained strains of D. melanogaster collected in various parts of Japan from 1952 to 1989 (Gamo et al, 1990) and recently collected from 1997 to 2001 (Itoh et al, 2001. Besides the E, H1, and H þ strains, we have found several E 0 strains that contain full-size hobo and/or deleted derivatives in older stocks and recently collected populations.…”
Section: Introductionmentioning
confidence: 99%